Paul Ehrlich's receptor immunology : the magnificent obsession - Silverstein, Arthur M. (Academic Press, 2002)
This book describes the background to Paul Ehrlich's immunological works and theories and delves into the substance of his experiments in great detail. By exploring these early developments in immunology, the book lays the foundation for modern concepts, providing immunologists, biomedical researchers, and students the context for the discoveries in their field. the selectionist theory of antibody formation kinetics of primary and secondary antibody response quantitative methods of measurement of antigens and antibody demonstration of passive transfer of immunity from mother to foetus.